Proceedings of the 16th International Conference on Multimodal Interaction 2014
DOI: 10.1145/2663204.2663273
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Users' Perceived Difficulty of Multi-Touch Gesture Articulation

Abstract: International audienceWe show that users are consistent in their assessments of the articulation difficulty of multi-touch gestures, even under the many degrees of freedom afforded by multi-touch input, such as (1) various number of fingers touching the surface, (2) various number of strokes that structure the gesture shape, and (3) single-handed and bimanual input. To understand more about perceived difficulty, we characterize gesture articulations captured under these conditions with geometric and kinematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
5
23
0
Order By: Relevance
“…Therefore, we confirmed previous results that the longer the gesture the more difficult it is perceived to be [17]. …”
Section: Perceived Gesture Difficultysupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, we confirmed previous results that the longer the gesture the more difficult it is perceived to be [17]. …”
Section: Perceived Gesture Difficultysupporting
confidence: 91%
“…These results are consistent with previous studies, both for sighted [17] and visually impaired people [10]. Regarding prior knowledge of gestures, although 26 participants said they had used some kind of mobile touchscreen, only half of them already knew the most popular gestures: swipe left and swipe up.…”
Section: Group Gesture Featuressupporting
confidence: 91%
See 1 more Smart Citation
“…Researchers have also looked at people's perceptions about gesture commands in order to identify perceptually-similar classes [19,22,30,31]. For example, Long et al [19] investigated the visual similarity of pen gestures and derived a computable model for perceptual similarity using gesture features, such as curviness, that correlated R 2 =.56 with user-reported similarity.…”
Section: Techniques To Study Gesture Articulationmentioning
confidence: 99%
“…Vatavu et al [31] found that subjects were highly consistent in estimating the execution difficulty of single-stroke gestures, leading to two estimation rules based on production time that approximated absolute and relative perceived difficulty with 75% and 90% accuracy, respectively. Recently, Rekik et al [22] extended the study to include multi-stroke gestures. Subjects were also consistent in their perception of gesture scale (e.g., large versus small gestures), which is predictable with 90% accuracy using a rule based on the area size of the gesture bounding box [30].…”
Section: Techniques To Study Gesture Articulationmentioning
confidence: 99%